PENINGKATAN KOMITMEN KINERJA PEGAWAI MELALUI KEDISIPLINAN, KOMUNIKASI, KEPEMIMPINAN DAN MOTIVASI PADA PUSAT PENGEMBANGAN PEMBERDAYAAN PENDIDIK DAN TENAGA KEPENDIDIKAN - Siswanto, Rahmat (Prodi Magister Manajemen FE-UST, 2018)
The aim of this research is to know the effect of discipline, communication, leadership and motivation in good work by partial and simultan for the Civil Government at the centre of development and efficiency the educator and staff of education (PPPPTK) Mathematic Yogyakarta. The population is all the staff in the centre of development and efficiency the educator and staff education (PPPPTK) Mathematic Yogyakarta has 172 staffs. By using technique of random sampling was got 114 sample of the staffs. The technique to take the data of this research by using questioner. The analysis used regression double linier. The result of the research can show that discipline in work, communication, leadership, motivation can give positive effect and significant to the commitment. Discipline, communication, leadership and motivation of work by simultan are have positive effect and significant to the commitment of work.   Keywords: Discipline, Communication, Leadership, Motivation, commitment